Uso de inaladores dosimetrados na população de adolescentes e adultos, com diagnóstico médico autorreferido de asma, enfisema e bronquite crônica, Pelotas, RS. - Oliveira, Paula Duarte de (2012)
Objective: to evaluate the characteristics of the users of metered-dose inhalers and its prevalence, among those who reported a diagnosis of asthma, bronchitis and/or emphysema. Methods: a population-based study in Pelotas, RS, Brazil, including 3,670 subjects aged 10 years or older. Results: About 10% of the sample referred at least one respiratory disease. Among these, 59% referred symptoms in the last year and of those, only half have used inhalers, showing difference between the quintiles of socioeconomic status (39% poorest quintile vs. 61% richest quintile p=0,01). There was no difference in the use of inhalers by age and sex. Regarding the pharmacological group, the emphysematous used a combination of bronchodilator (BD) plus corticosteroids in greater proportion than just BD. Only among those who reported a medical diagnosis of asthma and with actual symptoms, the proportion of use of inhalers was higher than 50%. Conclusion: metered-dose inhalers are underused among those who relate these diagnoses and the type of medicine used by the ones who referred emphysema is not in accordance with the recommendations in the consensus about these diseases.